Sistem Tanda Tangan Digital Menggunakan SHA-3 dan ECDSA (UNISTEK, 2023)
This research aims to implement an information security system for electronic documents using electronic signatures based on ECDSA (Elliptic Curve Digital Signature Algorithm) and SHA-3 (Secure Hash Algorithm 3) algorithms. This research was conducted to answer questions about the security and integrity protection of digital documents in today's digital age. The research method used is a randomized controlled experiment testing the effectiveness of a security system implemented in a simulated environment. The data obtained from this experiment were statistically analyzed with valid and reliable results. Research results show that implementing a security system with digital signatures based on ECDSA and SHA-3 effectively protects the security and integrity of digital documents. The ECDSA algorithm ensures the legitimacy and authentication of digital documents through a digital signature process using private and public keys. The SHA-3 algorithm is used as a strong hashing algorithm to compute hashes of digital documents to ensure data integrity. The results show that a security system implemented using digital signatures based on ECDSA and SHA-3 can provide a high level of security in protecting digital documents. Prevent unauthorized changes and tampering.